2016
DOI: 10.1016/j.porgcoat.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electrochemical noise measurement on an organically coated metal

Abstract: Electrochemical noise measurement (ENM) has found a credible place among the electrochemical methods applied to organic coatings, with a large number of reports in the literature of using the technique as a reliable method for the evaluation of the corrosion protection afforded by an organic coating on a metal surface. This has commonly been performed by calculating the noise resistance, Rn, or spectral noise resistance, Rsn, from the two main elements of electrochemical noise signal, the electrochemical curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…The authors present here a theoretical model for use of the SS technique of ENM based on a simple linear EEC. The analysis follows previous such efforts performed by Cottis et.al and Jamali et.al to elucidate the effects of solution resistance and coating impedance on ENM data respectively [34,35]. Experimental data demonstrating the effects of LRE impedance on a simple corrosion system of low carbon steel exposed to 3.5wt% NaCl solution is also presented.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The authors present here a theoretical model for use of the SS technique of ENM based on a simple linear EEC. The analysis follows previous such efforts performed by Cottis et.al and Jamali et.al to elucidate the effects of solution resistance and coating impedance on ENM data respectively [34,35]. Experimental data demonstrating the effects of LRE impedance on a simple corrosion system of low carbon steel exposed to 3.5wt% NaCl solution is also presented.…”
Section: Introductionmentioning
confidence: 85%
“…As with the earlier efforts by Cottis et.al and Jamali et.al, it is important for the purposes of our analysis to break down the complex ENM setups into simple linear EECs, and clarify a number of underlying assumptions [34,35]. It is important to note that the EEC and subsequent analysis for the SB technique presented here is ultimately identical to the analysis presented in earlier publications for the purpose of determining the effect of coating impedance and solution resistance respectively on ENM data [34,35]. As such, the analysis presented here derives the same equations, and is included merely for the sake of convenience and ease of comparison to the analysis of the SS technique.…”
Section: Theoretical Modelmentioning
confidence: 96%
“…As yet the modelling of these processes and how they lead to a value of Rn is poorly understood. Recent studies have shown the effect of the coating's ionic resistance on attenuating current noise signal in the specific case of fully disbonded coating from the metal substrate [12,79].…”
Section: Other Time Domain Analysis Methods (Mainly Bare Metal)mentioning
confidence: 99%
“…sodium and chloride) through the polymer film is the rate determining step in controlling the overall rate of the corrosion reaction. Hence the EN measurement of resistance becomes a measure of the rate of diffusion of ions through the polymeric structure [12]. 4 It should also be pointed out that ENM acquires mechanistic information about metal loss in uncoated systems such as the corrosion uniformity/localization which may not be acquired by other bulk electrochemical techniques such as EIS and DC resistance measurements [13].…”
mentioning
confidence: 99%
“…The authors, however, noted that the NOCS technique was more sensitive to interferences related to extraneous signals than the conventional standard bridge configuration. When applied for the investigation of coatings, EN analysis is also concerned with the measurement of the rate of diffusion of ions through the coatings; which is the rate determining step for the corrosion of a metallic substrate with an organic coating [125]. The application of EN analysis to study the corrosion behavior and coating-substrate interfacial properties of very high impedance coatings has, in turn, made it feasible to determine corrosion onset and to assess the effectiveness of surface pretreatment of metal before coating [126,127].…”
Section: Evaluation Of Organic Coatingsmentioning
confidence: 99%